Comparison of isometric strength men´s upper limbs from the Czech Republic with a group of athletes from different sectors - Vilim, M.; Juránková, M.; Janicková, P. (Journal of Human Sport & Exercise, 2015)
The aim of this work was to find out the strength difference of the static flexors of the hand between the dominant and non-dominant upper limbs of sportsmen from chosen branches and general population. A group of 20 sportsmen (10 tennis players and 10 javelin throwers) and a group of general population (252 probands from the whole Czech Republic area) took part in the measuring. All tested people were aged 18 - 29. The measured values (in kg) were obtained by means of a test of handheld dynamometry (digital handheld dynamometer). The measuring showed that sportsmen have higher values of dominant upper limb isometric strength than general population (58.2 kg and 53.8 kg). With the non-dominant upper limb, the situation is reverse: higher values were discovered with general population (51.2 kg) whereas with sportsmen it was only 50.1 kg. A substantially higher difference of isometric strength between the dominant and non-dominant hand was discovered with sportsmen (8.1 kg); this difference is much smaller (2.1 kg) with general population.